Dampak Pembelajaran dan Efek Katalitik OSCE pada Mahasiswa Tahun I,II, dan III Fakultas Kedokteran UGM - Triyani Triyani; Gandes Retno Rahayu; Efrayim Suryadi (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2014)
Background: OSCE is one of the assessments used in the Faculty of Medicine of Universitas Gadjah Mada, Yogyakarta since 1993. The uses of the OSCE as assessment tool have been widely proven. However, it also had limitations such as the presence of anxiety of the students and the high complexity of resources. This study aimed at finding out the impact of the OSCE on learning and its catalytic effects on the first, second and third year students of the Faculty of Medicine of Universitas Gadjah Mada.Method: In a qualitative method, data was collected using focus group discussion. There were 25 participants assigned to 3 groups, which were the group of the first year students, that of the second year students and that of the third year students. Samples were drawn using purposive sampling technique. The data was collected once the students have followed the OSCE. Analysis was made using Atlasti verion 6 and intercoding was conducted along with medical and health education experts.Results: The impacts of the OSCE were the learning strategy of the students more focused on clinical skills and their learning motivation increase. The OSCE caused anxiety of the students and they needed constructive feedback. The catalytic effects of the OSCE in the study were: It made the students more aware of the necessity to more diligently learn, to actively look for learning sources, to more creatively learn, to learn in a more integrated and comprehensive manner.Conclusion: The impact of the OSCE on learning was influenced by its organization and students’ characteristics. The positive catalytic effect of the OSCE on the students was that they needed standard OSCE. The study must be continued using other methods for example survey, cross-sectional or mixed methods.